2011
DOI: 10.1515/jpem.2011.023
|View full text |Cite
|
Sign up to set email alerts
|

Italian pediatric data support hypothesis that simultaneous epidemics of type 1 diabetes and type 2 diabetes/metabolic syndrome/obesity are polar opposite responses (i.e., symptoms) to a primary inflammatory condition

Abstract: We previously postulated that iatrogenic infl ammation caused epidemics of type 2 diabetes/metabolic syndrome/obesity by activating an immune suppressive cortisol response which protects against type 1 diabetes and other autoimmune diseases. In the current study, data on the incidence of obesity in different Italian provinces was compared with the incidence of type 1 diabetes in the same region. The association between obesity and type 1 diabetes was analyzed using Wilcoxon rank analysis. Results showed an inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our interest for these diseases depends from the fact that Southern Italy shows the highest rates of type2 diabetes/obesity [40] and, also, of liver cancer for Europe, mainly related to infection with hepatitis viruses (i.e. CHC) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our interest for these diseases depends from the fact that Southern Italy shows the highest rates of type2 diabetes/obesity [40] and, also, of liver cancer for Europe, mainly related to infection with hepatitis viruses (i.e. CHC) [41].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we report a simultaneous and comparative analysis of the serum levels of a large panel of cytokines, growth factors, chemokines, as well as of other cancer and diabetes biomarkers in patients with T2D, CHC, HCC and T2D-HCC by means of BioPlex assays. Our interest for these diseases depends from the fact that Southern Italy shows a high mortality trend for liver cancer in CHC patients [ 16 ] concomitantly with very high rates of T2D [ 17 ]. Recently we evaluated the cytokinome profile in patients with T2D and/or CHC infection or with CHC-related HCC suggesting some specific markers for the different stages of the diseases [ 8 9 , 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is released to stop tissue destruction and autoimmune processes. Classen (31) has reported that iatrogenic infl ammation activates immunosuppressive cortisol response, which protects against type 1 diabetes and other autoimmune diseases, but causes type 2 diabetes, MetS, and obesity. Persistently high cortisol levels cause a number of adverse reactions, as they disrupt normal physiological functions.…”
Section: Endocrine Factors and Metsmentioning
confidence: 99%